2008
DOI: 10.1103/physrevlett.100.033603
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Control of Nonadiabatic Alignment of Rotationally ColdN2Molecules with the Feedback of Degree of Alignment

Abstract: Nonadiabatic alignment of rotationally cold N2 molecules is optimally controlled by shaping femtosecond pump pulses with the feedback of degree of alignment evaluated by an ion imaging technique. The alignment is optimized by doubly peaked pulses with approximately equal intensities. A doubly peaked pulse with an appropriate interval can be regarded as a single pulse with a center trough based on the considerations from both time and frequency domains, suggesting that the effective duration of a doubly peaked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…This is desirable for applications where the presence of a strong laser field interferes. The impulsive alignment that can be achieved using a single laser pulse is intrinsically limited 13 but can be improved by applying a laser-pulse sequence 13,19 or an appropriately tailored laser-pulse profile 20,21 .The availability of aligned molecules has sparked the emergence of new techniques such as tomographic imaging of electronic orbitals 11 , and the observation of multicentre interference in highharmonic generation as a tool for structural determination 12 . Further improvements in the alignment of molecules are likely to enable new applications, such as diffractive imaging at emerging X-ray free-electron lasers such as LCLS at Stanford, XFEL at Hamburg and SCSS at 23 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is desirable for applications where the presence of a strong laser field interferes. The impulsive alignment that can be achieved using a single laser pulse is intrinsically limited 13 but can be improved by applying a laser-pulse sequence 13,19 or an appropriately tailored laser-pulse profile 20,21 .The availability of aligned molecules has sparked the emergence of new techniques such as tomographic imaging of electronic orbitals 11 , and the observation of multicentre interference in highharmonic generation as a tool for structural determination 12 . Further improvements in the alignment of molecules are likely to enable new applications, such as diffractive imaging at emerging X-ray free-electron lasers such as LCLS at Stanford, XFEL at Hamburg and SCSS at 23 .…”
mentioning
confidence: 99%
“…This is desirable for applications where the presence of a strong laser field interferes. The impulsive alignment that can be achieved using a single laser pulse is intrinsically limited 13 but can be improved by applying a laser-pulse sequence 13,19 or an appropriately tailored laser-pulse profile 20,21 .…”
mentioning
confidence: 99%
“…Different from the sample molecules at room temperature, the alignment is optimized by doubly peaked pulses with approximately equal intensities for rotationally cold molecules. 80 Based on the considerations in both temporal and frequency domains, it is found that the double-peaked pulse with an appropriate interval can induce nonadiabatic molecular alignment virtually equivalent to that induced by a single pulse with an appropriate duration.…”
Section: Enhancement Of Molecular Alignmentmentioning
confidence: 98%
“…The shaped femtosecond laser pulses have been widely used in the coherent control of the molecular ensembles. [20][21][22][23][24] Also, these phase-shaped laser pulses have been used in the rotational and vibrational control and further molecular alignment manipulation. [25][26][27] It has been demonstrated that the degree of the molecular alignment could be greatly enhanced by the phase-shaped laser pulses.…”
Section: Introductionmentioning
confidence: 99%